2006
DOI: 10.1021/om050869w
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Complexes with Metallocene-Bridged Bidentate Diphosphine Ligands:  Synthesis, Structure, and Catalytic Activity in Amination and Cross-Coupling Reactions

Abstract: The syntheses and characterization of series of new metallocene-bridged diphosphines and the structures of complexes of some of them with Pd(II) are reported. These complexes were examined as the catalysts in amination reactions of halogenoarenes and in the Suzuki reaction. The complexes based on ruthenocene (2) and osmocene (3) showed lower activities then the palladium complex with dppf in amination reactions and the same activities in the Suzuki reaction. New palladium complexes with the bidentate bulky and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 47 publications
(51 reference statements)
3
59
0
Order By: Relevance
“…The cationic palladium complexes 5-8 were prepared by treatment of the dichloride complexes 1-4 [5], with silver triflate in the presence of acetonitrile (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cationic palladium complexes 5-8 were prepared by treatment of the dichloride complexes 1-4 [5], with silver triflate in the presence of acetonitrile (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorus atoms are equivalent in [Fe(g 5 -C 5 H 4 -P{o-C 6 H 4 OMe} 2 ) 2 Pd(OTf)](OTf) (5) and [Fe(g 5 -C 5 H 4 P-{C 6 F 5 } 2 ) 2 Pd(NCMe)(OTf)](OTf) (8) and exhibit singlets at d 51.1, 17.2, respectively, in the 31 P{ 1 H} NMR spectra, which is consistent with complex cations being in fast exchange with solvent and triflate. The a-and b-cyclopentadienyl protons in the complexes with relatively small ortho-anisyl (5) and pentafluorophenyl (8) aryl substituents appear as non-resolved multiplets at d 4.74, 5.04 for 5 and at d 4.81, 5.35 for 8.…”
Section: Resultsmentioning
confidence: 99%
“…In only a very few examples, such as [(h 6 -C 6 H 6 )Cr(h 6 -C 6 F 5 )PPh 2 ] [7,8] and [Fe{h 5 -C 5 H 4 P(C 6 F 5 ) 2 } 2 ] [98], are substituents bound to a metal whilst phosphorus is not. The two most obvious effects of fluorination are the lowering of phosphine basicity and the increase in bulk, although other factors, such as ligand flexibility and the bite angle for bidentate ligands, are also important.…”
Section: Ligand Parametersmentioning
confidence: 99%
“…It was found that ligands bearing electron-withdrawing aryl substituents showed poor activity [98]. For the amination of 4-bromotoluene (Scheme 25) in dioxane at 100 8C, Fe(h 5 -C 5 H 4 PPh 2 ) 2 gave 63% conversion in 20 min, whereas Fe{h 5 -C 5 H 4 P(C 6 F 5 ) 2 } 2 gave only 13% conversion.…”
Section: Aminationmentioning
confidence: 99%
See 1 more Smart Citation